Bioremediation of Petroleum Contamination: A Short Review - Khan, Saimah; Tripathi, Ayush Kumar; Srivastava, Rohan; Saleem, Mohd Saad; Yeremenko, Sergiy; Sydorenko, Volodymyr (Ecological Questions, 2022)
The pros and cons of using the bioremediation method for the removal of petroleum pollutants are discussed in this review article. Other methods along with bioremediation have been used to remediate petroleum hydrocarbon contaminants in the past. Bioremediation is cheap and efficient method than any other because major constituents of the crude oils are biodegradable. Despite the fact that, as compared to physicochemical strategies, longer periods are normally required, complete pollutant degradation can be achieved, and no further containment of the contaminated matrix is required. According to hydrocarbon present in the contaminants different strategies and organism are used for the bioremediation. Common strategies include controlling environmental factors such as oxygen availability, hydrocarbon solubility, nutrient balance and managing hydrocarbon degrading bacteria by eliminating the rate limiting factors that may slow down the bioremediation rate. Microorganism dynamics during bioremediation is most important for understanding how they respond, adapt and remediate pollution. However, bioremediation can be considered one of the best technologies to deal with petroleum product contaminants.